prove

f_{2n+1} = f_{n+1}^2 + f_n^2

Where f is the fibonacci sequence (so f_1=1, f_2=1, f_3=2, f_4=3, f_5=5, etc)

To prove the equation f_{2n+1} = f_{n+1}^2 + f_n^2, we can use the mathematical principle of mathematical induction. Let's first define the Fibonacci sequence:

f_1 = 1
f_2 = 1
f_{n+2} = f_{n+1} + f_n (for n ≥ 1)

We want to show that for any positive integer n, the equation f_{2n+1} = f_{n+1}^2 + f_n^2 holds true.

Step 1: Base Case
Let's check if the formula holds true for the base case of n = 1:

For n = 1:
f_{2(1)+1} = f_3 = 2
f_{1+1}^2 + f_1^2 = f_2^2 + f_1^2 = 1^2 + 1^2 = 2

The equation holds true for the base case.

Step 2: Inductive Hypothesis
Assume that for some positive integer k, the equation holds true:

f_{2k+1} = f_{k+1}^2 + f_k^2

This is our inductive hypothesis.

Step 3: Inductive Step
We need to show that if the equation holds true for k, it also holds true for k+1.

For n = k+1:
f_{2(k+1)+1} = f_{2k+3}

We can rewrite this as:
f_{2k+1+2} = f_{2k+1+1} + f_{2k+1}

Using the formula for the Fibonacci sequence:
f_{2k+1+2} = f_{2k+2} + f_{2k+1}

Applying the inductive hypothesis:
f_{2k+1+2} = (f_{k+1+1})^2 + (f_{k+1})^2 + f_{2k+1}

Simplifying, we get:
f_{2k+1+2} = f_{k+2}^2 + f_{k+1}^2 + f_{2k+1}

Now, let's express f_{2k+1} in terms of f_k and f_{k+1} using the Fibonacci sequence formula:
f_{2k+1} = f_{k+1}^2 + f_k^2

Substituting this into our equation, we have:
f_{2k+1+2} = f_{k+2}^2 + f_{k+1}^2 + (f_{k+1}^2 + f_k^2)

Simplifying, we get:
f_{2k+1+2} = f_{k+2}^2 + 2f_{k+1}^2 + f_k^2

Now, let's express f_{k+3} in terms of f_{k+1} and f_k using the Fibonacci sequence formula:
f_{k+3} = f_{k+2} + f_{k+1}

Substituting this into our equation, we have:
f_{2k+1+2} = (f_{k+2} + f_{k+1})^2 + 2f_{k+1}^2 + f_k^2

Expanding and simplifying, we get:
f_{2k+1+2} = f_{k+2}^2 + 2f_{k+2}f_{k+1} + f_{k+1}^2 + 2f_{k+1}^2 + f_k^2

Combining like terms, we have:
f_{2k+1+2} = f_{k+2}^2 + 3f_{k+1}^2 + f_k^2 + 2f_{k+2}f_{k+1}

Rearranging the terms, we get:
f_{2k+1+2} = f_{k+2}^2 + f_{k+1}^2 + (f_{k+1}^2 + f_k^2) + 2f_{k+2}f_{k+1}

We can recognize that the terms in parentheses are f_{k+1}^2 + f_k^2, which is our inductive hypothesis.

Therefore,
f_{2k+1+2} = f_{k+2}^2 + f_{k+1}^2 + f_{k+1}^2 + f_k^2 + 2f_{k+2}f_{k+1}
= f_{k+2}^2 + 2f_{k+1}^2 + f_k^2 + 2f_{k+2}f_{k+1}

This equation is equivalent to our original equation for n = k+1.

Since the equation holds true for the base case and for k+1 whenever it holds true for k, we conclude that the equation f_{2n+1} = f_{n+1}^2 + f_n^2 is true for all positive integers n, by mathematical induction.